2021
DOI: 10.1007/s11356-021-16065-w
|View full text |Cite
|
Sign up to set email alerts
|

Exergy and energy analysis of a tubular solar still with and without fins: a comparative theoretical and experimental approach

Abstract: Today, availability of clean water is hard as the residents are expanding and moving fast to achieve rapid urbanization as a result need for clean water has been raised. Solar stills are the solution to desalinate to obtain pure water. This paper represents the theoretical and experimental study of tubular solar still with and without fins. The reading was recorded from 8:00 AM to 6:00 PM. Efficiency of TSS with fins and without fins are 23.39% and 13.76% respectively. The rate of irreversibility from the basi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The rate of irreversibility from the TSS cover is determined using eqn (7): 36 The rate of irreversibility from water is determined using eqn (8): 36 The rate of irreversibility from absorber is determined using eqn (9): 36 …”
Section: Evaporation and Exergy Efficiency Analysis Of Tubular Desali...mentioning
confidence: 99%
“…The rate of irreversibility from the TSS cover is determined using eqn (7): 36 The rate of irreversibility from water is determined using eqn (8): 36 The rate of irreversibility from absorber is determined using eqn (9): 36 …”
Section: Evaporation and Exergy Efficiency Analysis Of Tubular Desali...mentioning
confidence: 99%
“…It is concluded that system productivity is enhanced by 18% and 27.6% when vertical and inclined fins are used. Sathyamurthy et al 46 have carried out a theoretical and experimental study of TSS with and without fins. Fins in the TSS basin increased the amount of heat absorbed by the absorber basin due to the high surface area of the absorber plate, resulting in higher freshwater output than TSS without fins.…”
Section: Techniques To Improve the Performance Of Tssmentioning
confidence: 99%
“…The maximum enhancement of the freshwater productivity was 67.1% and obtained for wood thickness of 4 mm and nanoparticles concentration of 80 g/m 2 . Sathyamurthy et al 9 enhanced the performance of a TSS by using fins fixed along the trough transversely. They reported 22% enhancement in the hourly freshwater productivity while 2% and 7% for exergy and energy efficiency, respectively.…”
Section: Introductionmentioning
confidence: 99%